PENGARUH KEPUASAN KERJA, KEDISIPLINAN DAN MOTIVASI TERHADAP KINERJA TENAGA KEPENDIDIKAN POLTEKKES KEMENKES SURAKARTA KAMPUS II - Rohmat Rohmat (Master of Public Administration, Universitas Slamet Riyadi, 2021)
The performance of the teaching staff is a supporting factor that cannot be ignored in achieving the educational goals of the tertiary institution. Educational staff have the duty to support the running of the education process in tertiary institutions through administrative services for the implementation of an effective and efficient educational process. The objectives in this study are to: 1) Know the effect of job satisfaction on the performance of educational staff 2) Know the effect of discipline on the performance of educational staff 3) Know the influence of motivation on the performance of educational personnel and 4) Know the effect of job satisfaction, discipline and motivation on the performance of educational staff. This type of research is a survey and classified in explanatory research. This research was conducted at Campus II Health Polytechnic (Poltekkes) Surakarta. The study population of all educational staff at Campus II Surakarta Health Polytechnic totaling 46 people and the whole was used as a sample with census techniques. Data collection techniques using observation and questionnaires. Data analysis techniques using multiple linear regression. The results showed that job satisfaction had a positive and significant effect on the performance of the teaching staff at Campus II Surakarta Health Polytechnic. Discipline has a positive and significant effect on the performance of teaching staff at Campus II Health Polytechnic Surakarta. Work motivation has a positive and significant effect on the performance of teaching staff at Campus II Health Polytechnic Surakarta. Job satisfaction, discipline and work motivation simultaneously influence the performance of the teaching staff at Campus II Health Polytechnic Surakarta. Suggestions should be given to the leadership to increase the provision of salary on a regular basis as well as provide promotional opportunities for educational staff who excel. the leadership conducts regular supervision of the performance of the education staff.